Then and Now: The Context of Continuity - Joseph Biondo; Dan Silberman (Oz, 2015)
An admiration of a mundane material reality can develop from the recognition that things just are as they are. There is nothing metaphysical beyond the bricks and stones and, as Peter Zumthor suggests, we can admire a tree for its just being there.